Spotting Bubbles: A Two-Pillar Framework for Policy Makers - Bradley A. Jones (Journal of Banking and Financial Economics)
In the aftermath of the global fi nancial crisis, the issue of how best to identify speculative bubbles remains in fl ux. This owes to the diffi culty of disentangling irrational investor exuberance from the rational response to lower risk, based on price behavior alone. In response, I introduce a twopillar (price and quantity) approach for fi nancial market surveillance. While asset pricing models comprise a valuable component of the surveillance toolkit, risk taking behavior, and fi nancial vulnerabilities more generally, can also be refl ected in subtler, non-price terms. Though policy makers will always encounter uncertainty when attempting to measure imbalances in fi nancial markets, ‘perfect should not be the enemy of the good.’ In this spirit, the framework in this paper seems to capture some of the stylized facts of asset booms and busts, and thus could offer policy makers a practical guide as to when to consider leaning against the wind.